2008
DOI: 10.1093/intqhc/mzn021
|View full text |Cite
|
Sign up to set email alerts
|

Developing an automated speech-recognition telephone diabetes intervention

Abstract: While some patients expressed negative attitudes toward automated speech recognition telephone systems generally, most felt that a variety of functions of such a system could be beneficial to their diabetes care. In-depth interviews resulted in substantive input from health plan members for the design of an automated telephone outreach system to supplement in-person physician-patient communication in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…9 Other voice recognition technologies have recently been used to promote treatment adherence in asthma 10 and diabetes self-management. 11 In addition, text messaging has been used to support adolescents with asthma 27 and diabetes. 28 Email interventions have been introduced to improve blood pressure treatment adherence, 12 and a variety of web-based interventions have been used to improve smoking cessation, 13 weight loss, 14 hypertension, 12 and chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…9 Other voice recognition technologies have recently been used to promote treatment adherence in asthma 10 and diabetes self-management. 11 In addition, text messaging has been used to support adolescents with asthma 27 and diabetes. 28 Email interventions have been introduced to improve blood pressure treatment adherence, 12 and a variety of web-based interventions have been used to improve smoking cessation, 13 weight loss, 14 hypertension, 12 and chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…We developed the intervention based on prior studies (68). In particular, we conducted a series of interviews with Harvard Pilgrim patients and physicians to characterize their willingness to interact with ATO-SR and identified topics of interest (8). The computerized system placed three calls to the participants' home telephone numbers, encouraging the participants to fulfill recommended testing if it had not been performed in the preceding year.…”
Section: Methodsmentioning
confidence: 99%
“…However, studies noted that those with hearing impairment may have difficulty participating in a phone survey and some populations may not trust reporting information to a machine (Stuart et al, 2003;Brodey et al, 2005;Goldman et al, 2008;Naylor et al, 2008;Dalal et al, 2010;Rose et al, 2010a;2010b;Graham et al, 2012;Skolarus et al, 2012). However, studies noted that those with hearing impairment may have difficulty participating in a phone survey and some populations may not trust reporting information to a machine (Stuart et al, 2003;Brodey et al, 2005;Goldman et al, 2008;Naylor et al, 2008;Dalal et al, 2010;Rose et al, 2010a;2010b;Graham et al, 2012;Skolarus et al, 2012).…”
Section: Data Qualitymentioning
confidence: 99%
“…However, Rodriguez et al (2006) reported that a mailed survey was cheaper than IVR in their study and IVR costs increased when low response rates required crossover mailing. Some studies used the technology for service delivery or clinical care including for monitoring health outcomes, reminders, interventions and disease management (Reid et al, 2007;Goldman et al, 2008;Naylor et al, 2008;Sikorskii et al, 2009;Bender et al, 2010;Kempe et al, 2012;Greaney et al, 2012;Houser et al, 2013). Some studies used the technology for service delivery or clinical care including for monitoring health outcomes, reminders, interventions and disease management (Reid et al, 2007;Goldman et al, 2008;Naylor et al, 2008;Sikorskii et al, 2009;Bender et al, 2010;Kempe et al, 2012;Greaney et al, 2012;Houser et al, 2013).…”
Section: Costsmentioning
confidence: 99%